Aggregation‐Induced Nonlinear Optical Effects of AIEgen Nanocrystals for Ultradeep In Vivo Bioimaging. Issue 44 (16th September 2019) - Zheng, Zheng; Li, Dongyu; Liu, Zhiyang; Peng, Hui‐Qing; Sung, Herman H. Y.; Kwok, Ryan T. K.; Williams, Ian D.; Lam, Jacky W. Y.; Qian, Jun; Tang, Ben Zhong
Abstract: Nonlinear optical microscopy has become a powerful tool in bioimaging research due to its unique capabilities of deep optical sectioning, high‐spatial‐resolution imaging, and 3D reconstruction of biological specimens. Developing organic fluorescent probes with strong nonlinear optical effects, in particular third‐harmonic generation (THG), is promising for exploiting nonlinear microscopic imaging for biomedical applications. Herein, a simple method for preparing organic nanocrystals based on an aggregation‐induced emission (AIE) luminogen (DCCN) with bright near‐infrared emission is successfully demonstrated. Aggregation‐induced nonlinear optical effects, including two‐photon fluorescence (2PF), three‐photon fluorescence (3PF), and THG, of DCCN are observed in nanoparticles, especially for crystalline nanoparticles. The nanocrystals of DCCN are successfully applied for 2PF microscopy at 1040 nm NIR‐II excitation and THG microscopy at 1560 nm NIR‐II excitation, respectively, to reconstruct the 3D vasculature of the mouse cerebral vasculature. Impressively, the THG microscopy provides much higher spatial resolution and brightness than the 2PF microscopy and can visualize small vessels with diameters of ≈2.7 µm at the deepest depth of 800 µm in a mouse brain. Thus, this is expected to inspire new insights into the development of advanced AIE materials with multiple nonlinearity, in particular THG, for multimodal nonlinear optical microscopy. Abstract : Aggregation‐induced nonlinear optical effects, in particular third‐harmonic generation, of an aggregation‐induced emission luminogen (AIEgen) are observed in nanoparticles, especially for crystalline nanoparticles. AIEgen nanocrystals enable ultradeep intravital third‐harmonic generation imaging (up to 800 µm) of mouse cerebral vasculature with high spatial resolution (≈2.7 µm) at the deepest depth of 800 µm, much superior to two‐ and three‐photon fluorescence imaging.